2012
DOI: 10.1371/journal.pgen.1002898
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Genes Related to Cochlear Biology Is Strongly Associated with Adult-Onset Deafness in Border Collies

Abstract: Domestic dogs can suffer from hearing losses that can have profound impacts on working ability and quality of life. We have identified a type of adult-onset hearing loss in Border Collies that appears to have a genetic cause, with an earlier age of onset (3–5 years) than typically expected for aging dogs (8–10 years). Studying this complex trait within pure breeds of dog may greatly increase our ability to identify genomic regions associated with risk of hearing impairment in dogs and in humans. We performed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…The loss had begun at about 5 years of age, which ruled out presbycusis as a likely cause, and several had been BAER tested as hearing at earlier ages. The loss was gradual, had no gender predilection, and appeared to follow an AD pattern ( 146 , 147 ).…”
Section: Deafness In Domestic Animal Speciesmentioning
confidence: 99%
“…The loss had begun at about 5 years of age, which ruled out presbycusis as a likely cause, and several had been BAER tested as hearing at earlier ages. The loss was gradual, had no gender predilection, and appeared to follow an AD pattern ( 146 , 147 ).…”
Section: Deafness In Domestic Animal Speciesmentioning
confidence: 99%
“…By most accounts, the use of GWAS to locate heritable traits has been wildly successful in dogs, identifying loci for eye diseases, skin disorders, cancer, deafness, neurological disorders, heart disease, and a host of other disorders (Ahonen et al 2013, Grall et al 2012, Karyadi et al 2013, Olsson et al 2011, Tengvall et al 2013, Yokoyama et al 2012), as well as morphological traits (Boyko et al 2010, Vaysse et al 2011), including body size, skull shape, leg length, and fur type and color (Cadieu et al 2009, Clark et al 2006, Dreger et al 2013, Drögemüller et al 2008, Karlsson et al 2007, Parker et al 2009, Rimbault et al 2013, Schoenebeck et al 2012). Loci of large effect, a fraction of which are described below, were rapidly identified in population-based approaches that compared SNP allele frequencies with a myriad of phenotypic traits.…”
Section: Genetic Approaches To Mapping Canine Traits and Diseasesmentioning
confidence: 99%
“…Although BAER hearing tests can be used to diagnose dogs with reduced hearing to an advanced stage and complete deafness, no diagnostic test is currently available for early identification of those Border Collies likely to become deaf. A recent study using some of the dogs reported here, but assuming an autosomal mode of inheritance and an earlier age of onset, and a GWAS approach, reported a region on CFA6 that appeared to be implicated [ 3 ]. An earlier smaller GWAS by some members of this group suggested a region on CFA18 [ 4 ].…”
Section: Discussionmentioning
confidence: 99%